Evaluating the Cost for Robotic vs "Non-Robotic" Transhiatal Esophagectomy. Issue 3 (March 2022) - Ross, Sharona B.; Rayman, Shlomi; Thomas, Ja'Karri; Peek, George; Crespo, Kaitlyn; Syblis, Cameron; Sucandy, Iswanto; Rosemurgy, Alexander
Introduction: This study was undertaken to analyze and compare the cost of robotic transhiatal esophagectomy (THE) to "non-robotic" THE (ie, "open" and laparoscopic). Methods: With IRB approval, we prospectively followed 82 patients who underwent THE. We analyzed clinical outcomes and perioperative charges and costs associated with THE. To compare profitability, the robotic approach was analyzed against "non-robotic" approaches of THE using F-test, Mann-Whitney U test/Student's t-test, and Fisher's exact test. Statistical significance was reported as P ≤0.05. Data are presented as median (mean ± SD). Results: 67 patients underwent the robotic approach, and 15 patients underwent "non-robotic" approach; 4 were "open" and 11 were laparoscopic. 79 patients had adenocarcinoma. Operative duration for robotic THE was 327 (331 ± 82.8) vs 213 (225 ± 62.0) minutes ( P = 0.0001) and estimated blood loss was 150 (184 ± 136.1) vs 300 (476 ± 708.7) mL ( P = 0.0001). Length of stay was 7 (11 ± 11.8) vs 8 (12 ± 10.6) days ( P = 0.76). 16 patients had post-operative complications with a Clavien-Dindo score of three or more. Hospital charges for robotic THE were 197, 405 (259, 936 ± 203, 630.8) vs "non-robotic" THE 159, 588 (201, 565 ± 185, 763.5) ( P = 0.31). Cost of care for robotic THE was 34, 822 (48, 844 ± 45, 832.8) vs "non-robotic" THE was 23, 939 (39, 386 ± 44, 827.2) ( P = 0.47). Payment received for robotic THE was 14, 365 (30, 003 ± 40, 874.7) vs "non-robotic" THE was 28, 080 (41, 087 ± 44, 509.1) ( P = 0.41). 15% of robotic operations were profitable vs 13% of "non-robotic" operations. Conclusions: Patients were predominantly older overweight men who had adenocarcinoma of the esophagus. The robotic approach had increased operative time and minimal blood loss. More than a fourth of operations included concomitant procedures. Patients were discharged approximately one week after THE. Overall, the robotic approach has no apparent significant differences in charges, cost, or profitability.